Future data and security engineering : 6th International Conference, FDSE 2019, Nha Trang City, Vietnam, November 27-29, 2019, proceedings /: 6th International Conference, FDSE 2019, Nha Trang City, Vietnam, November 27-29, 2019, proceedings. ([2019]) - Unknown
No abstract available